Identification and Analysis of Factors Influencing the Development of Sports in the Islamic Republic of Iran’s Army Using Foresight Methodology (Focusing on Health and Lifestyle) - Karimzadeh, Mohammad Sadegh; Naderinasab, Mahdi; Taheri, Morteza; Biniyas, Sied Abbas (International Journal of Sport Studies for Health, 2025)
Objective: Sport has gained attention from health policymakers as a significant factor in promoting health. Therefore, sport is of crucial importance and requires the identification of relevant drivers and scenarios. The aim of this study is to identify and analyze the factors influencing the development of sports in the Islamic Republic of Iran’s Army using the foresight methodology. Material and Methods: This research is applied-developmental in nature and descriptive-analytical based on data collection and analysis methods. Results: According to the findings, 30 drivers were identified in six general categories: social, technological, environmental, economic, political, and value-based. Subsequently, considering three dimensions—critical uncertainty, the wellness movement and lifestyle, the management skills of army sports managers, and sufficient sports budget—four alternative future scenarios were created: Bright World (Green Land Scenario), the Land of Sports and Health Seekers, the Static Land, and the Desert Land. Conclusion: According to the research results, in the policy-making for the development of sports and health in the Islamic Republic of Iran’s Army, the drivers, particularly the strategic drivers of the wellness movement and lifestyle, the management skills of army sports managers, and a sufficient budget, should be taken into consideration for greater success in this field.